Mimosa pudica: Experiment of light stimulation on plant movement - Bjorn, Chong Jin (2016)
A native weed to Central and South America, Mimosa pudica commonly known as the “sensitive plant” can be found almost worldwide. In some countries such as Australia, this species is considered invasive. Across Singapore, they thrive in large open fields. Mimosa pudica display a unique defence mechanism for protection from animals and insects, where upon introduction of environmental stimuli, its leaves close and petiole hang down. This movement is known as seismonastic movement. Environmental stimuli can be in the form of heat, electrical, mechanical or/and light. This has spurred many studies and research to further understand the movement of Mimosa pudica. This study focuses on the reaction time of Mimosa pudica with various colored light stimuli. By applying different light stimulations, this project attempts to understand the point of fatigue and recovery time of Mimosa pudica.